Preseason Adductor Squeeze Strength in 303 Spanish Male Soccer Athletes: A Cross-sectional Study - Ernest Esteve; Michael Skovdal Rathleff; Jordi Vicens‐Bordas; Mikkel Bek Clausen; Per Hölmich; L. Sala; Kristian Thorborg (2018)
Background: Hip adductor muscle weakness and a history of groin injury both have been identified as strong risk factors for sustaining a new groin injury. Current groin pain and age have been associated with hip adductor strength. These factors could be related, but this has never been investigated. Purpose: To investigate whether soccer athletes with past-season groin pain and with different durations of past-season groin pain had lower preseason hip adductor squeeze strength compared with those without past-season groin pain. We also investigated whether differences in preseason hip adductor squeeze strength in relation to past-season groin pain and duration were influenced by current groin pain and age. Study Design: Cross-sectional study; Level of evidence, 3. Methods: In total, 303 male soccer athletes (mean age, 23 ± 4 years; mean weight, 74.0 ± 7.9 kg; mean height, 178.1 ± 6.3 cm) were included in this study. Self-reported data regarding current groin pain, past-season groin pain, and duration were collected. Hip adductor squeeze strength was obtained using 2 different reliable testing procedures: (1) the short-lever (resistance placed between the knees, feet at the examination bed, and 45° of hip flexion) and (2) the long-lever (resistance placed between the ankles and 0° of hip flexion) squeeze tests. Results: There was no difference between those with (n = 123) and without (n = 180) past-season groin pain for hip adductor squeeze strength when adjusting for current groin pain and age. However, athletes with past-season groin pain lasting longer than 6 weeks (n = 27) showed 11.5% and 15.3% lower values on the short-lever (P = .006) and long-lever (P < .001) hip adductor squeeze strength tests, respectively, compared with those without past-season groin pain. Conclusion: Male soccer athletes with past-season groin pain lasting longer than 6 weeks are likely to begin the next season with a high-risk groin injury profile, including a history of groin pain and hip adduction weakness.